Underground Water-Level Monitoring by Integrated Study of Geoelectric, Logging, Cutting and Pumping Data in Industrial Area of Candi Sub-District, Sidoarjo (Jurnal Pendidikan Fisika Indonesia, 2019)
Monitoring of underground water level with integrated data of geoelectric, logging, cutting and pumping has been done in industrial area of Candi Sub-district, Sidoarjo, which is productive aquifers with widespread area. The integrated study showed that monitoring aquifers in industrial wells has carried out at depths of 140-165 meters. The lithology of the aquifer layer consists of sand layer, clay, and gravel with a low resistivity value of 14.7 to 46.8 ohmmeters. The monitoring results showed that the use of underground water at night was higher than the day and the use on workday was higher than on holiday. The stable debit generated by monitoring wells was 8.41 lt/sec and the groundwater level would return to stable 2.17 meters if the well is rested for 3 hours. The implication of this study was monitorable of the dynamics underground water levels periodically.